Parental Support in the Learning of Students with Deaf and Hard of Hearing at Home - Paskaran, Thilakavathy; Mohd Yasin, Mohd Hanafi (Department of Special Education, 2020)
Education policy encourages parental support as a mechanism for improving learning outcomes. This survey was conducted to determine how well parents can contribute to academic achievement in the special education needs (SEN) among deaf and hard of hearing students. This study uses the Epstein Parent involvement Model and Bronfenbrenner Ecological Theory. A set of 20 questionnaire items with a five-point Likert scale adapted from this study by the Ministry of Education Malaysia was used. A total of 22 students from a secondary school in Seremban were selected for the purpose of this study. The data were analyzed descriptively and in inference using Statistical Package for the Social Sciences (SPSS) version 25 to obtain scores. The Pearson correlation test shows that the relationship between deaf and hard of hearing students' academic achievement and parental support is a strong and significant positive relationship (p <0.05). The findings show low parental support with deaf and hard of hearing students' academic achievement, which is also a low level. Overall, the study found that parents need to pay close attention to providing a home-based learning environment, social interaction, communication, and academic support to help children develop their potential self and achieve better student academic achievement.